catena-Poly[[dichloridozinc(II)]-μ-1,1′-(hexane-1,6-diyl)diimidazole-κ(2) N (3):N (3′)] - Bao, Wen-Li (International Union of Crystallography, 2009)
In the structure of the polymeric title compound, [ZnCl(2)(C(12)H(18)N(4))](n) or [ZnCl(2)(L)](n), where L = 1,1′-(hexane-1,6-diyl)diimidazole, the Zn(II) centre is coordinated by two N atoms of two different L ligands and by two chloride anions in a distorted tetrahedral geometry. The organic ligand links adjacent metals to form a polymeric chain along the c axis. The chains are further connected into layers parallel to the bc plane by intermolecular C—H⋯Cl hydrogen bonds. Two C atoms of the central hexyl chain are disordered over two positions with site-occupancy factors of 0.5.